Preface (Вопросы атомной науки и техники, 2001)
This issue of PROBLEMS OF ATOMIC SCIENCE AND TECHNOLOGY contains papers presented at
the International Conference on Quantum Electrodynamics and Statistical Physics, "QEDSP2001", Kharkov,
Ukraine. The Conference was held at the National Science Center "Kharkov Institute of Physics and Technology"
(NSC KIPT) from October 30 to November 3, 2001. It was dedicated to the 90th birthday anniversary of
Academician Alexander Il’ich Akhiezer (October 31, 1911 − May 4, 2000) who made an outstanding contribution to
theoretical physics.